2011
DOI: 10.1016/j.cbpa.2011.06.014
|View full text |Cite
|
Sign up to set email alerts
|

The neuronal control of cardiac functions in Molluscs

Abstract: In this manuscript, I review the current and relevant classical studies on properties of the Mollusca heart and their central nervous system including ganglia, neurons, and nerves involved in cardiomodulation. Similar to mammalian brain hemispheres, these invertebrates possess symmetrical pairs of ganglia albeit visceral (only one) ganglion and the parietal ganglia (the right ganglion is bigger than the left one). Furthermore, there are two major regulatory drives into the compartments (pericard, auricle, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 183 publications
(248 reference statements)
0
33
0
2
Order By: Relevance
“…Amygdala dependent fear learning involves NE as a main neurotransmitter, since the post-training intracranial injection of 1 g NE led to amnesia in rats 24 h after passive avoidance task (Kesner & Ellis, 1983). The pathological release of catecholamine NE in mammals including humans occurs in comparable manner to invertebrates (Kodirov, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Amygdala dependent fear learning involves NE as a main neurotransmitter, since the post-training intracranial injection of 1 g NE led to amnesia in rats 24 h after passive avoidance task (Kesner & Ellis, 1983). The pathological release of catecholamine NE in mammals including humans occurs in comparable manner to invertebrates (Kodirov, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, muscle (Dyachuk, 2013) and neural (Odintsova et al, 2010) cell differentiation depend on functional peptides and growth factors found in the ECM, which constitute basic requirements for muscle assembly, neural guidance, and synaptogenesis. In addition, endocrine chemical messengers target special cell receptors and trigger genetic neurohormonal control, therefore mediating an interactive effect on ciliary (Carroll and Catapane, 2007) and cardiac (Kodirov, 2011) functions, signalization (Fabbri and Capuzzo, 2010), and immune defence (Ramos MartiNez et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…La elección del organismo modelo a utilizar dependerá del estudio que se hará, en este trabajo se utilizó el corazón de T. stultorum debido a que presenta un bajo costo de adquisición, es fácil de manipular y tiene una respuesta uniforme [3,4] . Al igual que en corazones humanos, la superficie endocárdica de corazones de moluscos es similar a los músculos suaves de mamí-feros, además de que su frecuencia cardíaca puede llegar a valores comparables a los de humanos (60 latidos por minuto), este valor puede ser modificado por factores de estrés o compuestos químicos como fármacos [5,6] .…”
Section: Introductionunclassified